Pilot testing of CO2 capture from a coal-fired power plant—Part 1: Sorbent characterization. Issue 2 (9th May 2019) - Sjostrom, Sharon; Senior, Constance
Abstract: Post-combustion CO2 capture followed by sequestration is one of the only feasible means to significantly reduce CO2 emissions from existing fossil-fuel-fired power plants. This paper is Part 1 of a two-part paper highlighting key results from a project sponsored by the US Department of Energy and supported by industrial groups with the objective of demonstrating the viability of solid sorbents for CO2 capture. The overall objective of the effort was to validate solid sorbent-based post-combustion CO2 capture through slipstream pilot testing at a coal-fired power plant using a temperature-swing adsorption process. In Part 1 of this work, the results from laboratory characterization of the sorbent selected for the pilot-scale demonstration are presented. A great deal of research related to sorbent development and evaluation has occurred to date but, for the most part, these promising materials have yet to be paired with a feasible process and demonstrated at the pilot scale. The sorbent selected for pilot-scale evaluation under this project consisted of an ion-exchange resin that incorporated amines that were covalently bonded to the substrate. During the sorbent characterization portion of this work, the sorbent was characterized by a range of methods intended to provide information to support the design and operation of the pilot-scale CO2 -capture process, including equilibrium adsorption isotherms, adsorption and regeneration kinetics, impact of moisture and oxygen on CO2 working capacity, sorbent thermal properties, sorbent strength and attrition, and optimum particle-size distribution. This paper reports results from sorbent characterization testing and how these characteristics influenced the type and size of the CO2 -capture process equipment. In Part 2 of this work, results from tests of 1-MWe pilot-scale process equipment loaded with the sorbent described in Part 1 will be presented and analysed.